Students’ literary literacy across cognitive processes in reading A.A. Navis’ short story Robohnya Surau Kami - Ramadhanti, Dina; Yanda, Diyan Permata; Sinaga, Arta Losena Br (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Students’ ability to interpret implicit meanings, symbolism, and social criticism in literary texts remains limited, despite these competencies being fundamental to literary literacy and higher-order reading comprehension. Existing studies have predominantly assessed general reading proficiency, with relatively little attention to the cognitive processes underlying literary reading. This study aims to examine students’ literary reading abilities based on cognitive processes and identify their levels of literary literacy through their responses to A.A. Navis’s short story Robohnya Surau Kami. The study is grounded in the cognitive reading process framework and Kintsch’s Constructionâ€“Integration Model, which conceptualizes reading comprehension as the dynamic construction of meaning through interactions among textual information, prior knowledge, and inferential reasoning. Employing a quantitative descriptive design, the study involved 31 Indonesian senior high school students who completed a multiple-choice literary literacy test measuring six cognitive processes: searching for information, understanding, analyzing, inferring, synthesizing, and evaluating. Descriptive statistical analysis revealed an overall mean score of 67.08, indicating a moderate level of literary reading ability. Students demonstrated the strongest performance in synthesizing and evaluating but showed the weakest performance in inferential reasoning, highlighting difficulties in constructing implicit meanings. Literary literacy levels ranged from basic comprehension to advanced evaluative reading, with most students clustered at the understanding and analytical levels. These findings suggest that literary literacy develops through non-linear cognitive processes shaped by the semantic complexity and interpretive demands of literary texts, underscoring the need for explicit instructional support to strengthen students’ inferential and interpretive reading skills.